The Social Condition of England’s Women in 18th Century Reflected in Pride and Prejudice by Jane Austen - Bahri A. Bohang, Muthmainnah; Magfirah, Sulmi; Adi Nugroho, Dwi (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This paper aims to: (1) know what the intrinsic aspects of Pride and Prejudice, (2) describe how the social condition of England’s women is in 18th century reflected in “Pride and Prejudice” and (3) analyze what the economical influence towards England’s women in “Pride and Prejudice”. This study employs a qualitative research method with a literary analysis approach. The analysis of this thesis uses genetic structuralism. It is conducted by analyzing the intrinsic elements which consists of plot, characters, setting, and theme. Besides, the writer also analyzes the extrinsic elements by observing from the sociology, history and other aspects outside the literary work. The genetic structuralism analysis used to find the intrinsic elements in this novel, the social condition of England’s women in 18th century reflected in “Pride and Prejudice” and also the economical influence towards England’s women in “Pride and Prejudice”. This analysis shows that in the 18th century, England’s women get inequality gender in the society. Education, politic, and occupation are not allowed to them.  Economical matter pushed them to marry with a rich and high-status men to lead a secure life.